Gastropod Diversity as a Bioindicator of the Heavy Metal Iron (Fe) Around the East Coast River of Surabaya - Abdillah, Afrisal Amar; Arifin, Moch; Wijaya, Kemal (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Surabaya is a large city with a high number of industries and population density, so there is potential for heavy metal iron (Fe) pollution which affects environmental quality and the sustainability of aquatic living creatures. Gastropods are one of the macrofauna that have difficulty moving from place to place, so their presence is a bioindicator of an area with heavy metal Iron (Fe) pollution. Gastropod sampling was carried out using the transect sampling method with sampling locations spread across three locations, namely around the Kebon Agung River, Tambak Oso River and Jagir River. The diversity index was calculated using the Shannon-Wiener diversity index. The concentration of iron (Fe) metal pollutants was analyzed using AAS (Atomic Absoption Spectrophotometer). The relationship between heavy metal Fe accumulation and gastropods was analyzed using the Pearson correlation test. The research results showed that there were 14 types of gastropods with a medium diversity index (H') with values between 1.34-2.03 and an accumulation of the heavy metal iron 35994.7-44986.3 (ppm). Keywords: Abundance, Diversity Index, Gastropods, Heavy metal iron (Fe), Surabaya East Coast River.